Ethyl tert-butyl ether (EtBE) degradation by an algal-bacterial culture obtained from contaminated groundwater. (1st January 2019) - van der Waals, Marcelle J.; Plugge, Caroline; Meima-Franke, Marion; de Waard, Pieter; Bodelier, Paul L.E.; Smidt, Hauke; Gerritse, Jan
Abstract: EtBE is a fuel oxygenate that is synthesized from (bio)ethanol and fossil-based isobutylene, and replaces the fossil-based MtBE. Biodegradation of EtBE to harmless metabolites or end products can reduce the environmental and human health risks after accidental release. In this study, an algal-bacterial culture enriched from contaminated groundwater was used to (i) assess the potential for EtBE degradation, (ii) resolve the EtBE degradation pathway and (iii) characterize the phylogenetic composition of the bacterial community involved in EtBE degradation in contaminated groundwater. In an unamended microcosm, algal growth was observed after eight weeks when exposed to a day-night light cycle. In the fed-batch reactor, oxygen produced by the algae Scenedesmus and Chlorella was used by bacteria to degrade 50 μM EtBE replenishments with a cumulative total of 1250 μM in a day/night cycle (650 lux), over a period of 913 days. The microbial community in the fed-batch reactor degraded EtBE, using a P450 monooxygenase and 2-hydroxyisobutyryl-CoA mutase, to tert -butyl alcohol (TBA), ethanol and CO2 as determined using 13 C nuclear magnetic resonance spectroscopy (NMR) and gas chromatography. Stable isotope probing (SIP) with 13 C6 labeled EtBE in a fed-batch vessel showed no significant difference in community profiles of the 13 C and 12 C enriched DNA fractions, with representatives of the families Halomonadaceae, Shewanellaceae, Rhodocyclaceae, Oxalobacteraceae, Comamonadaceae, Sphingomonadaceae, Hyphomicrobiaceae, Candidatus Moranbacteria, Omnitrophica, Anaerolineaceae, Nocardiaceae, and Blastocatellaceae . This is the first study describing micro-oxic degradation of EtBE by an algal-bacterial culture. This algal-bacterial culture has advantages compared with conventional aerobic treatments: (i) a lower risk of EtBE evaporation and (ii) no need for external oxygen supply in the presence of light. This study provides novel leads towards future possibilities to implement algal-bacterial consortia in field-scale groundwater or wastewater treatment. Graphical abstract: Highlights: Micro-oxic EtBE degradation in an algal-bacterial culture in the presence of light. Micro-oxic EtBE derived metabolites include tert -butyl alcohol, ethanol and CO2 . EtBE degradation involves activity of bacterial cytochrome P450-monooxygenase. Micro-oxic EtBE degradation involves activity of 2-hydroxyisobutyryl-CoA mutase.